VOICES OF RESISTANCE: FEMALE AGENCY IN CHITRA BANERJEE’S THE OLEANDER GIRL - Ms. Arunanjali Keshari, Prof. Kalpana Agrawal (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This research paper aims to investigate acts of individual resistance by analyzing the behavioural tendencies of various characters in Chitra Banerjee’s novel, Oleander Girl. A meticulous examination of certain characters reveals how they challenge the patriarchal hierarchy through indifference, stoic silence, anger, strategic compliance, and assertion. These acts of resistance can be either overt or covert. "declared acts of resistance" refers to actions and gestures demonstrating disagreement or disapproval of the established order in clear and specific terms. Conversely, "undeclared acts" are concealed methods of resistance that operate discreetly. In situations where open confrontation is neither feasible nor desirable, tacit opposition to authority is often preferred. It has been observed that characters in Divakaruni’s work resort to such forms of resistance despite their seemingly non-combative nature.